The Sensitivity of Leersia hexandra Sw. to Gamma-Ray Irradiation - Sukmasari, Pritha Kartika; Widoretno, Wahyu; Siswanto, Dian (Graduate School, Universitas Brawijaya, 2021)
Gamma-ray irradiation as a physical mutagen has high penetrating power. Therefore, it is most often used to increase genetic variability or produce new mutant plants. This research was conducted to obtain the lethal dose of gamma-rays in Leersia hexandra plants. The used plant part was a single node stolon which had a length of 10 cm with the node in the middle of the stolon. The irradiation doses given were 0, 25, 50, 75, 100 Gy. Stolons were inserted into plastic clips and irradiated using a Cobalt-60 gamma irradiation source at the Center for Irradiation and Radioisotope Applications (PAIR), National Nuclear Energy Agency (BATAN) Jakarta. Gamma-irradiation has a significant effect on inhibiting shoot growth. The growth of irradiated Leersia hexandra with the best number of plants and the highest shoots was obtained at a dose of 25 Gy and decreased with increasing irradiation dose. The lethal dose (LD50) was determined eight days after irradiation using CurveExpert 1.4 software. Leersia hexandra plants that can sprout and regenerate followed the linear equation y = 1.02 - 7.5x with LD50 at 68.85 Gy and LD20 at 29.36 Gy.Keywords: gamma irradiation, genetic variation, Leersia hexandra, lethal dose, mutant plant.